1975
DOI: 10.1029/rs010i001p00107
|View full text |Cite
|
Sign up to set email alerts
|

Scintillations due to a concentrated layer with a power‐law turbulence spectrum

Abstract: The spatial spectrum of intensity fluctuations due to a concentrated layer of turbulence is derived from the parabolic wave equation. The spectrum of refractive index fluctuations is taken to be an unmodified power law of arbitrary strength, with exponent a, 2 ( a ( 6. For 2 • a ( 4 it is shown that the intensity spectra for a plane wave can be expressed in terms of a single parameter U, which is the Born approximation to m a, the normalized variance of intensity fluctuation. For U << 1 the Born approximation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
2

Year Published

1979
1979
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(53 citation statements)
references
References 29 publications
1
50
2
Order By: Relevance
“…The strength of the turbulence or scattering structure, C s , has been used to describe the irregularity strength and is given by (Rumsey, 1975;Rino, 1979):…”
Section: Phase Screen Theorymentioning
confidence: 99%
“…The strength of the turbulence or scattering structure, C s , has been used to describe the irregularity strength and is given by (Rumsey, 1975;Rino, 1979):…”
Section: Phase Screen Theorymentioning
confidence: 99%
“…This assumption is commonly used in astrophysical situations (Prokhorov et al 1975;Rumsey 1975;Mercier 1962;Salpeter 1967), and a treatment incorporating the extended nature of the scattering medium introduces no additional effects relevant to the present discussion.…”
Section: The Scattering Modelmentioning
confidence: 99%
“…The two are related under the assumption that the phase fluctuations are frozen into the scattering screen (e.g. Rumsey 1975). The spatial power spectrum of intensity fluctuations, P I (κ), is related to the auto-correlation of the intensity fluctuations by a Fourier transform…”
Section: Variability Of An Extended Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…[19,27] have shown that under strong scint illat ion, the power spectrum will be broadened at the low-frequency-end while the slope of the roll off will remain the same as under single scattering. They also found that the correlat ion distance or the autocorrelat ion interval (t ime ôm required for the autocorrelat ion coefficient to decrease to 0.5) would decrease with increasing transmitted frequency under weak scint illat ion but would increase with mult iple scatter under strong scint illat ion.…”
Section: B Strong Scintillationmentioning
confidence: 99%